EFFECT OF NPK FERTILIZERS IN RELATION TO SEED YIELD IN BRASSICA JUNCEA (L) VAR. PUSA BOLD - L. P. DALAL; P. B. NANDKAR (The Bioscan, 2011)
An field experiment was conducted on cotton black soil to investigate the effect of various levels of NPK on the plant height, number of branches and on the seed yield. NPK application from 20:10:10 kg/ha, progressively and significantly enhanced the seed yield. The maximum seed yield was with the application of 50:40:25 kg NPK /ha, while the NPK application at the rate of 60:50:30 and 70:50:35 kg NPK/ha, receives decrease in yield. Similarly their was no enhancement in plant height, number of branches per plant and number of pod per plant in higher doses.